Human rights violations in the practice of Ulwaluko: A social work perspective - Kasa, Luvo (Edelweiss Applied Science and Technology, 2025)
This study explores the intersection of traditional male circumcision, or ulwaluko, among the amaXhosa in South Africa and human rights concerns. While ulwaluko is a deeply rooted cultural practice and a rite of passage into adulthood, it has also been associated with severe human rights violations, including physical harm, psychological distress, and inadequate medical oversight. This research employs a qualitative methodology, utilizing thematic content analysis to examine data from academic literature, policies, and community perspectives. Anchored in Anti-Oppressive Practice, the study highlights systemic inequalities affecting initiates and the lack of social work interventions. The findings indicate a pressing need for policy reform, integration of social work practices, and increased oversight to protect the well-being of initiates. This research contributes to the discourse on balancing cultural traditions with human rights protections and provides recommendations for improving the safety and dignity of initiates within ulwaluko.